Social computing and social media : design, human behavior and analytics : 11th International Conference, SCSM 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, proceedings, part 1 /: design, human behavior and analytics : 11th International Conference, SCSM 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, proceedings, part 1. (2019) - Unknown
No abstract available